2022
DOI: 10.30783/nevsosbilen.1167272
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Pandemi̇ Süreci̇nde Öğretmenleri̇n Uzaktan Eği̇ti̇m Deneyi̇mleri̇

Abstract: Bu araştırmada COVID 19 sürecinde öğretmenlerin uzaktan eğitim deneyimlerinin ortaya konması amaçlanmıştır; araştırma nitel araştırma yöntemi kullanılarak yürütülmüştür ve olgubilim desenindedir. Araştırmanın çalışma grubunu 2020-2021 öğretim yılında Diyarbakır’da görev yapmakta olan 15 resmi ortaokul öğretmeni oluşturmaktadır. Çalışma grubunun belirlenmesinde maksimum çeşitlilik örneklemi kullanılmıştır. Araştırmada veri toplama aracı olarak araştırmacılar tarafından geliştirilen yarı yapılandırılmış̧ görüşme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…In their study, Bıyıklı and Özgür (2021) suggested that, for synchronous distance education to be effective, instructional methods and techniques should be altered, motivating activities should be conducted, healthy communication with students should be established, learning gaps should be identified and promptly addressed, lessons should be meticulously planned, and collaboration with other teachers in the school should be encouraged. Some other studies (Aral & Kadan, 2021;Avcı & Akdeniz, 2021;Can & Nikolayidis, 2022;Kazak & Karamehmetoğlu, 2023;Koşar & Bakır, 2022;Özdoğan & Berkant, 2020) (Aral & Kadan, 2021;Bıyıklı & Özgür, 2021;Can & Nikolayidis, 2022;Kazak & Karamehmetoğlu, 2023;Koşar & Bakır, 2022;Özdoğan & Berkant, 2020;Taş, 2021), improving the assessment and evaluation system (Özdoğan & Berkant, 2020), preparing school administrators and teachers for emergency distance education (Avcı & Akdeniz, 2021), and providing them with in-service training on distance education (Balaman & Hanbay-Tiryaki, 2021;Can & Nikolayidis, 2022;Taş, 2021). It can be noted that the research results align with the existing literature, and based on these findings, the following recommendations can be made:…”
Section: Extended Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, Bıyıklı and Özgür (2021) suggested that, for synchronous distance education to be effective, instructional methods and techniques should be altered, motivating activities should be conducted, healthy communication with students should be established, learning gaps should be identified and promptly addressed, lessons should be meticulously planned, and collaboration with other teachers in the school should be encouraged. Some other studies (Aral & Kadan, 2021;Avcı & Akdeniz, 2021;Can & Nikolayidis, 2022;Kazak & Karamehmetoğlu, 2023;Koşar & Bakır, 2022;Özdoğan & Berkant, 2020) (Aral & Kadan, 2021;Bıyıklı & Özgür, 2021;Can & Nikolayidis, 2022;Kazak & Karamehmetoğlu, 2023;Koşar & Bakır, 2022;Özdoğan & Berkant, 2020;Taş, 2021), improving the assessment and evaluation system (Özdoğan & Berkant, 2020), preparing school administrators and teachers for emergency distance education (Avcı & Akdeniz, 2021), and providing them with in-service training on distance education (Balaman & Hanbay-Tiryaki, 2021;Can & Nikolayidis, 2022;Taş, 2021). It can be noted that the research results align with the existing literature, and based on these findings, the following recommendations can be made:…”
Section: Extended Summarymentioning
confidence: 99%
“…There are limited number of studies in the literature identifying the problems encountered by teachers working at all educational levels from preschool to high school during the emergency distance education process (Avcı & Akdeniz, 2021;Bıyıklı & Özgür, 2021;Can & Nikolayidis, 2022). Indeed, previous studies in the literature (Altıntaş-Yüksel, 2021;Aral & Kadan, 2021;Avcı & Akdeniz, 2021;Balaman & Hanbay-Tiryaki, 2021;Başaran et al, 2020;Can & Nikolayidis, 2022;Can & Ozan, 2021;Fidan, 2020;Han et al, 2021;Kazak & Karamehmetoğlu, 2023;Koşar & Bakır, 2022;Özdoğan & Berkant, 2020;Pokhrel & Chhetri, 2021;Shim & Lee, 2020;UNESCO, 2020;Taş, 2021) also highlighted that teachers faced challenges related to technology, particularly infrastructure and hardware failures as well as internet access issues.…”
Section: Extended Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Yakın zamanda yaşanılan küresel Covid salgını sürecinde ise ilkokuldan üniversiteye kadar başta canlı dersler olmak üzere eğitim ve öğretimin her basamağında çevrim içi araçların kullanılması bu araçların kullanımına yönelik olumlu sonuçlar doğurmuştur. Koşar-Bakır (2022: 2233 yapmış oldukları araştırmaya katılan ortaokul öğretmenlerinin salgın süreciyle birlikte eğitim ve teknolojiyi ilişkilendirerek daha önce kullanmadıkları dijital program ve uygulamaları kullanmaya başladıklarını, bu durumun da teknoloji kullanım becerilerini geliştirdiği ifade etmişlerdir. Han-Demirbilek vd.…”
Section: çEvrim İçi öLçme Ve Değerlendirme Araçlarıunclassified